Improving Patient Experience In Healthcare Processes: Discrete Event Simulation-based Approach (Tanzania Journal for Population studies and Development, 2023)
In an effort to improve patient experience, hospitals face pressure to streamline care processes. This study used discrete event simulation to investigate strategies to improve patient experience in the treatment process characterized by long waiting times. The study proposes a new model of care whereby trained non-surgeons, such as physiotherapists and registered nurses, are involved in treating patients with minor orthopaedic cases. This proposition is expected to have a positive effect by reducing patient waiting time by approximately 73%. Given that developing countries are facing a critical shortage of healthcare personnel, the realized capacity can save the lives of patients that are not supposed to be seen by surgeons due to inadequate capacity. This study informs healthcare managers and policy makers that patient experience in the treatment process can be improved by adopting less-costly strategies, such as using a mid-level workforce to increase workforce capacity and minimize waiting time. This study focused on a single care process with a limited number of variables. It is proposed that subsequent studies could include more than one care process and more variables.